Steam temperature control of hydro-steam distillation process using self-tuning fuzzy fractional-order PI controller / Mazidah Tajjudin - Tajjudin, Mazidah (Institute of Graduate Studies, UiTM, 2015)
Essential oil is the volatile extracts of botanical material and it is being used to promote health and human well-being because of its therapeutic effect. Essential oil is commercially extracted using distillation method which requires heat in order to break the oil glands during the process. Unfortunately, the oil quality obtained using this method is uncertain because chemical compounds in the oil are exposed to decomposition or transformation at high temperature. Hence, this research proposed a novel approach of closed-loop temperature control using a new self-tuning fuzzy fractional-order PI (FOPI) controller to realize low temperature essential oil extraction for a hydro-steam distillation process. The controller will regulate the steam temperature at a desired level to protect the oil from excessive heat…